An interesting carcinoid tumor case followed up thirteen years - Selim GÜREL,; Kadir DEMİR,; Güngör BOZTAŞ,; İzzet ROZANES,; Sebahattin KAYMAKOĞLU,; Sadakat ÖZDİL,; Zeynel MUNGAN,; Oktay YEĞİNSU,; Atilla ÖKTEN, (Turkish Journal of Gastroenterology, 2019)
-